2008
DOI: 10.1080/14786410701654602
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of hexane extract from bark ofJuniperus brevifolia

Abstract: The phytochemical analysis of the bark of Juniperus brevifolia was undertaken for the first time. The GC-MS analysis of the hexane extract from bark of "cedro-do-mato" (J. brevifolia) allowed to identify three rare compounds for the first time in Juniperus genus: 6,7-dehydroferrugin-12-methyl ether, 11-hydroxy-6,7-dehydroferruginol and 6,7-dehydrohinokiol. The results also showed that the chemical composition of the extract were essentially abietane-type diterpenoids with alcohol function (44.9%) and with carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The chemical composition of J. brevifolia essential oils has been reported by Adams [10] and Da Silva [11]. The GC-MS analysis of the hexane extract from the bark of this species showed essentially abietane-type diterpenoids [12]. We report herein the cytotoxic and antimicrobial activities of extracts from J. brevifolia and the isolation of compounds from the dichloromethane extract of the leaves, together with the cytotoxic activity of five of these compounds against HeLa and Vero cells.…”
Section: Absupporting
confidence: 56%
“…The chemical composition of J. brevifolia essential oils has been reported by Adams [10] and Da Silva [11]. The GC-MS analysis of the hexane extract from the bark of this species showed essentially abietane-type diterpenoids [12]. We report herein the cytotoxic and antimicrobial activities of extracts from J. brevifolia and the isolation of compounds from the dichloromethane extract of the leaves, together with the cytotoxic activity of five of these compounds against HeLa and Vero cells.…”
Section: Absupporting
confidence: 56%
“…Chemical characterization of n-hexane fraction (Green et al, 2011) has been reported to contain non polar compounds (Ahmad et al, 2011). Different types of terpenoids, fatty acids and sterols have been reported from the hexane extracts of botanicals (Seca and Silva, 2008). Antimicrobial activity of terpenoids (Ulubelen et al, 2003), fatty acids (Skalicka-Woźniak et al, 2010), volatile oils (Dorman and Deans, 2000) and sterols (Zhao et al, 2005) has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…J. conferta Parl.) and Juniperus formosana Hayata [ 12 , 13 , 16 , 54 , 55 ]. Sugiol presents hepatoprotective [ 51 ] and antioxidant properties [ 56 ].…”
Section: Bioactive Secondary Metabolites From Juniperus mentioning
confidence: 99%
“…[ 12 , 13 ]. It is the most abundant compound in the hexane extract of J. brevifolia bark (11 mg of compound by 100 mg of extract) [ 54 ], being also found in species from other genus [ 63 ]. This compound seems to be a good bet towards new interesting active drugs development since it displays a range of interesting bioactivities such as antibacterial [ 64 , 65 , 66 ], antimycobacterial [ 38 ], antileishmanial [ 36 ], antimalarial [ 67 , 68 ], antistaphylococcal activity caused by efflux inhibitory properties [ 69 ], as well as nematicidal activity and antifouling attributes [ 36 ].…”
Section: Bioactive Secondary Metabolites From Juniperus mentioning
confidence: 99%